Injustice Continuity: Gender Inequality in Japan in the 21st Century - Mukhlis Arifin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The issue of gender equality is still a problem attached to the Japanese economic, social, political, and cultural system. The movement for Japanese liberation efforts and strived since the middle of the twentieth century is still stagnating. This problem remains inseparable from how stakeholders maintain a conservative thought. Women in the domestic sphere and women are the person who does not have the capacities as men are still the basis for reason. This paper will review how gender inequality is still a severe issue that needs to be fought for in the twenty-first century.Isu kesetaraan gender masih berupa permasalahan yang erat melekat dalam sistem ekonomi, sosial, politik dan budaya Jepang. Pergerakan upaya liberasi Jepang yang telah diperjuangkan sejak pertengahan abad ke dua puluh sampai saat ini masih mengalami stagnansi. Keberlanjutan isu ini tidak terlepas dari bagaimana sebuah konstruksi berpikir konservatif tetap dipertahankan oleh pemangku kepentingan. Perempuan dengan ranah domestik dan perempuan tidak memiliki kapasitas yang mumpuni daripada laki-laki masih menjadi dasar berpikir dalam permasalahan ini. Tulisan ini akan mengulas bagaimana isu ketimpangan gender masih merupakan isu serius yang perlu diperjuangkan di abad ke dua puluh satu.